Post-Pandemic MSME Performance Revitalization in Jambi Province - Ekasari, Novita; Rosmeli,; Nurhayani, (Archives of Business Research, 2023)
This study aims to describe revitalization performance of MSMEs in Jambi Province after the Covid 19 Pandemic through product innovation, digitalization and business networks carried out by MSME business actors. The sample from the research consisted of 100 MSMEs which are Micro, Small and Medium Enterprises who have implemented digitalization in their businesses spread across 10 districts and cities in Jambi province. The method used in this research is a survey method and primary data was obtained from distributing questionnaires in combination using Google Form and carried out directly by visiting respondents. This research uses the Smart PLS analysis tool. The results of the research show that digitalization, product innovation and business networks have a positive influence on business performance both directly and indirectly, but with a relatively small percentage of influence, so there is still a need for maximization so that it can significantly bring positive impact on the growth of MSME businesses in Jambi province.